INFLUENCE OF PRINCIPALS' TRANSFORMATIVE CORPORATE LEADERSHIP STYLE ON TEACHERS' JOB COMMITMENT IN PUBLIC SECONDARY SCHOOLS IN ATHI RIVER SUB COUNTY, MACHAKOS COUNTY, KENYA. - Peter, Damaris Ngina; Kalai, Dr. Jeremiah M (African Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to analyse influence of principals' transformative corporate leadership style on teachers' job commitment in public secondary schools in Athi river sub county, Machakos county, Kenya. Methodology: The study used correlation research design to collect data from principals, deputy principals and teachers in public primary schools in Athi River Sub County. The total number of respondents was 13 principals, 13 deputy principals and, 260 teachers and thus the total target population was 286. The researcher used census approach to select all the schools' heads and their deputies and stratified random sampling to select 104 teachers. The analysis was done by descriptive statistics using Statistical Package for Social Sciences version 21.0. In addition, Pearson's correlation analysis and regression analysis were used to establish the relationship between the study variables. Results: The study found that idealized influence and teachers' job commitment were positively and significant related, further inspired motivation and teachers' job commitment were positively significant related, also intellectual stimulation and teachers' job commitment were positively and significantly related while finally +individualized considerations and teachers' job commitment were also positively and significantly related. Unique contribution to theory, practice and policy: The study therefore recommends that there is need for principals in public secondary schools to adopt transformation leadership styles so as to improve on teachers' job commitment.